(3YdGL GdQHh hMei GdbT (B/s - (3SejOS, Lhfs; (3GdOGQ GdYQHjI ddYdhe (B((3HjQhJ(B).s (3eQcR GdJYQjH hGdHQeLIs ((3HjQhJ (B- (3dHfGf(B:s (3GdOGQ GdYQHjI ddYdhe,s, 1996)
(3GdYfGUQ GdeTJQcI Hjf GdQHh hMei GdbT(B-(3eQV GdMSGSjI hGdMSGSjGJ GdeNJdaI(B-(3GdhSGFd GdWHjI deYGdLI GdQHh hMei GdbT(B-(3GcJTGa GdCWYeI GdeSHHI ddMSGSjI(B-(3EHWGd GdSehe hGdZPGA GdCeKd ddQHh hMei GdbT(B-(3gd GdaW GdeHjV YfUQ cGef aj MGdI GdQHh Ch Mei GdbT YfOc(B-(3GdCOhjI GdZPGFjI GdeSGYOI ddQHh hMei GdbT(B-(3OhQ GdPgf GdehLg aj GdGfOeGd GdPGJj(B-(3GdWad GdeUGH HGdQHh(B-(3cja JSGYO eDjfGJ GdghGA MGdGJ GdQHh hMei GdbT(B-(3ELQGAGJ GdESYGa GdChdj bUjQI GdCeO(B.s
Keywords: (3GdQHhs; (3Mei GdcdCs; (3CeQGV LgGR GdJfaSs